Strategy for cost efficiency calculation of the adoption cost of the multi-cloud solution through the deliverable-oriented breakdown - Дудка, О. О. (My University, 2022)
The main reason for usage of multi-cloud solutions is cost effectiveness. The accuracy of the cost benefits analysis that should be used in decision making process is directly related to the approach for the cost of development and cost of operation efforts calculation.
Keywords: quality attributes; multi-cloud; cost benefit analysis; cost efficiency; WBS